Presentation, Modeling and Experiments of an Electrostatic Actuator Based Catom for Programmable Matter - Romain Catry; Abdenbi Mohand-Ousaid; Micky Rakotondrabe; Philippe Lutz (Actuators, 2020)
Nowadays, the concept of programmable matter paves the way for promising applications such as reshaping an object to test different configurations, modeling or rapid prototyping. Based on elementary modules, such matter can be arranged and disassembled easily according to the needs of the designers. Several solutions have been proposed to implement this concept. Most of them are based on modular self-reconfigurable robotics (SMR) that can work together and move relatively to one another in order to change their configuration. Achieving such behavior requires to solve some technological challenges in particular module’s geometry and actuation. In this paper, we build and develop a proof of concept for a catom based on electrostatic actuation. The modeling and analysis of the actuator functioning as catom is given after a comparison of various possible actuation. Simulations as well as experiments validations are afterwards carried out to confirm and demonstrate the efficiency of electrostatic actuation to achieve latching capabilities of the proposed catom.